Optimalisasi Limbah Sekam Padi Sebagai Alternatif Pupuk Organik di Desa Bondrang Kecamatan Sawoo Kabupaten Ponorogo - Near Anggreini Hesti Noviana; Abim Nurrochim; Desi (Institut Agama Islam Negeri Ponorogo, 2023)
The village of Bondrang is located in the Sawoo district, Ponorogo County, East Java Province. The majority of the inhabitants in Bondrang Village are farmers because of the large land area that is used to grow crops. However, nowadays the government limits the distribution of fertilizer subsidies, so society has suffered from a shortage of fertilizer subsidies. Seeing the potential of agriculture that exists in Bondrang Village, we held training for the management of Sekam Padi as an Alternative Organic fertilizer. This is very important to help the community of Bondrang village use the natural wealth that it has so that it can optimize the use of organic fertilizer. Asset-Based Community Development Method (ABCD) In the execution of the activities, the participants were very enthusiastic about following a series of events until their completion. Participants actively participated in the pelatiha activities, and as a follow-up to the training activities, the planting activities of the physic garden (Toga) were held with the mothers of the members of the PKK to support the government program of Bondrang Village.